A power comparison of homogeneity tests in mixtures of exponentials - Karl Mosler; Wilfried Seidel; Christoph Jaschinger (University of Cologne, Seminar of Economic and Social Statistics, 1997)
The empirical power of several test procedures is studied which test for homogeneity against mixtures of exponential distributions.
Keywords: 330